2006
DOI: 10.1039/b610123b
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanics approach to mapping the conformational space of diaryl and triarylphosphines

Abstract: A molecular mechanics force field has been developed which accurately reproduces experimental solid state structures and conformer interconversion barriers for a series of sterically congested diaryl and triaryl phosphines and some of their chalcogenide and Cr(CO)5 derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…39 It has been found that tris-ortho-tolyl phosphine adopts only two (exo 2 and exo 3 ) out of the four possible conformations (exo 0 , exo 1 , exo 2 and exo 3 ) in crystal structures. [39][40][41][42] Baber et al have noted that the exo 3 conformation is preferred in metal complexes with low steric demand (two and three coordinate complexes, and some tetrahedral systems), while square planar or octahedral complexes feature ligands with an exo 2 conformation. 42 The (EF) 6 embrace is hindered and not possible when the exo 2 conformation is adopted, therefore the extra stability that the (EF) 6 embrace imparts on the crystal packing is likely to favour the exo 3 conformation over the exo 2 whenever sterically possible.…”
Section: Structural Relationships Between Tolyl-substituted R 3 Ei 2 ...mentioning
confidence: 99%
“…39 It has been found that tris-ortho-tolyl phosphine adopts only two (exo 2 and exo 3 ) out of the four possible conformations (exo 0 , exo 1 , exo 2 and exo 3 ) in crystal structures. [39][40][41][42] Baber et al have noted that the exo 3 conformation is preferred in metal complexes with low steric demand (two and three coordinate complexes, and some tetrahedral systems), while square planar or octahedral complexes feature ligands with an exo 2 conformation. 42 The (EF) 6 embrace is hindered and not possible when the exo 2 conformation is adopted, therefore the extra stability that the (EF) 6 embrace imparts on the crystal packing is likely to favour the exo 3 conformation over the exo 2 whenever sterically possible.…”
Section: Structural Relationships Between Tolyl-substituted R 3 Ei 2 ...mentioning
confidence: 99%
“…The parent imidazole compound, 2-(2 0 -tert-butylphenyl)-4,5-diphenylimidazole, 1, (Scheme 1) was synthesised using a 3 step procedure consisting of modifications of known methods. This briefly comprised the conversion of 2-tert-butylaniline to 2-tert-butyliodobenzene 19 via the diazonium salt, lithium-halogen exchange with n-BuLi and quenching with N,N-dimethylformamide to produce 2-tert-butylbenzaldehyde. 20 This was followed by a condensation reaction with benzil and ammonium acetate in acetic acid to form the imidazole ring under microwave irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis starts with aryl bromides 1 and 2 , prepared from the corresponding commercially available aniline derivatives using a Sandmeyer reaction 30 (Scheme ). The addition of magnesium metal to the aryl bromide ( 1 or 2 ) in tetrahydrofuran (THF) generates the respective Grignard reagents, which are then treated with ClP(NEt 2 ) 2 31.…”
Section: Resultsmentioning
confidence: 99%